Researcb on Name Lookup in Named Data Networking - Bin Liu; Yi Wang (Dianxin kexue)
Named data networking（NDN）proposed as a new future architecture for the internet, aims to satisfy the requirement of information sharing among the users. NDN applies the hierarchical names to identify contents, route packets and retrieve information. Given the massive amount of contents and the longest prefix matching principle, achieving high speed name lookup exhibits a big challenge to implement NDN in real networks. The technical challenges of name lookup were firstly analyzed, then the main techniques to achieve wire-speed name lookup and their corresponding research results were introduced.